Mandibular gnathobases of marine planktonic copepods – feeding tools with complex micro- and nanoscale composite architectures - Michels, Jan; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2015)
Copepods are dominant members of the marine zooplankton. Their diets often comprise large proportions of diatom taxa whose silicified frustules are mechanically stable and offer protection against grazers. Despite of this protection, many copepod species are able to efficiently break even the most stable frustule types. This ability requires specific feeding tools with mechanically adapted architectures, compositions and properties. When ingesting food, the copepods use the gnathobases of their mandibles to grab and, if necessary, crush and mince the food items. The morphology of these gnathobases is related to the diets of the copepods. Gnathobases of copepod species that mainly feed on phytoplankton feature compact and stable tooth-like structures, so-called teeth. In several copepod species these gnathobase teeth have been found to contain silica. Recent studies revealed that the siliceous teeth are complex microscale composites with silica-containing cap-like structures located on chitinous exoskeleton sockets that are connected with rubber-like bearings formed by structures with high proportions of the soft and elastic protein resilin. In addition, the silica-containing cap-like structures exhibit a nanoscale composite architecture. They contain some amorphous silica and large proportions of the crystalline silica type α-cristobalite and are pervaded by a fine chitinous fibre network that very likely serves as a scaffold during the silicification process. All these intricate composite structures are assumed to be the result of a coevolution between the copepod gnathobases and diatom frustules in an evolutionary arms race. The composites very likely increase both the performance of the siliceous teeth and their resistance to mechanical damage, and it is conceivable that their development has favoured the copepods’ dominance of the marine zooplankton observed today.
Keywords: crystalline silica; diatom frustule; mandibular gnathobase; marine planktonic copepod; resilin

Copepod Evolution - Huys, R.; Boxshall, G. A. (The Ray Society, 1991)

The Open Sea. The World of Plankton - Hardy, A. (Collins, 1970)

(untitled) - Humes, A. G. (Hydrobiologia, 1994)

(untitled) - Longhurst, A. R. (Prog. Oceanogr., 1985)

(untitled) - Verity, P. G.; Smetacek, V. (Mar. Ecol. Prog. Ser., 1996)

(untitled) - Turner, J. T. (Zool. Stud., 2004)

(untitled) - Smetacek, V. (Protist, 1999)

(untitled) - Armbrust, E. V. (Nature, 2009)

(untitled) - Michels, J.; Büntzow, M. (J. Microsc. (Oxford, U.K.), 2010)

Imaging Marine Life: Macrophotography and Microscopy Approaches for Marine Biology - Michels, J. (Confocal Laser Scanning Microscopy – Detailed Three-dimensional Morphological Imaging of Marine Organisms, 2013)

(untitled) - Michels, J.; Gorb, S. N. (J. Microsc. (Oxford, U.K.), 2012)

(untitled) - Koehl, M. A. R.; Strickler, J. R. (Limnol. Oceanogr., 1981)

(untitled) - Paffenhöfer, G.-A.; Strickler, J. R.; Alcaraz, M. (Mar. Biol. (Heidelberg, Ger.), 1982)

(untitled) - Strickler, J. R. (Science, 1982)

(untitled) - Price, H. J.; Paffenhöfer, G.-A.; Strickler, J. R. (Limnol. Oceanogr., 1983)

(untitled) - Bundy, M. H.; Vanderploeg, H. A. (J. Plankton Res., 2002)

(untitled) - Malkiel, E.; Sheng, J.; Katz, J.; Strickler, J. R. (J. Exp. Biol., 2003)

(untitled) - Koehl, M. A. R. (J. Biomech., 2004)

(untitled) - Anraku, M.; Omori, M. (Limnol. Oceanogr., 1963)

(untitled) - Arashkevich, Ye. G. (Oceanology (Engl. Transl.), 1969)

Functional Morphology of Feeding and Grooming in Crustacea - Schnack, S. B. (Functional Morphology of Feeding Appendages in Calanoid Copepods, 1989)

(untitled) - Ohtsuka, S.; Onbé, T. (Mar. Biol. (Heidelberg, Ger.), 1991)

(untitled) - Itoh, K. (Bull. Plankton Soc. Jpn., 1970)

(untitled) - Michels, J.; Schnack-Schiel, S. B. (Mar. Biol. (Heidelberg, Ger.), 2005)

(untitled) - Nishida, S.; Ohtsuka, S. (Mar. Biol. (Heidelberg, Ger.), 1996)

(untitled) - Michels, J. (J. Microsc. (Oxford, U.K.), 2007)

(untitled) - Beklemishev, K. V. (Dokl. Akad. Nauk. SSSR, 1954)

(untitled) - Sullivan, B. K.; Miller, C. B.; Peterson, W. T.; Soeldner, A. H. (Mar. Biol. (Heidelberg, Ger.), 1975)

Geographical and Seasonal Variability of Marine Plankton - Vyshkvartseva, N. V. (Structure of the Mandibles in the Genus Calanus s.l. in Relation to Latitudinal Zonality, 1975)

(untitled) - Miller, C. B.; Nelson, D. M.; Guillard, R. R. L.; Woodward, B. L. (Biol. Bull. (Woods Hole, MA, U.S.A.), 1980)

(untitled) - Miller, C. B.; Nelson, D. M.; Weiss, C.; Soeldner, A. H. (Mar. Biol. (Heidelberg, Ger.), 1990)

(untitled) - Michels, J.; Vogt, J.; Gorb, S. N. (Sci. Rep., 2012)

(untitled) - Michels, J.; Vogt, J.; Simon, P.; Gorb, S. N. (Zoology (Munich, Ger.))

(untitled) - Bechstein, K.; Michels, J.; Vogt, J.; Schwartze, G. C.; Vogt, C. (Anal. Bioanal. Chem., 2011)

(untitled) - Ehrlich, H. (Int. Geol. Rev., 2010)

(untitled) - Brunner, E.; Richthammer, P.; Ehrlich, H.; Paasch, S.; Simon, P.; Ueberlein, S.; van Pée, K.-H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hamm, C. E.; Merkel, R.; Springer, O.; Jurkojc, P.; Maier, C.; Prechtel, K.; Smetacek, V. (Nature, 2003)

(untitled) - Tréguer, P.; Nelson, D. M.; Van Bennekom, A. J.; DeMaster, D. J.; Leynaert, A.; Quéguiner, B. (Science, 1995)

An Introduction to the Chemistry of the Sea - Pilson, M. E. Q. (Cambridge University Press, 2012)

(untitled) - Hillerton, J. E.; Robertson, B.; Vincent, J. F. V. (J. Stored Prod. Res., 1984)

(untitled) - Quicke, D. L. J.; Wyeth, P.; Fawke, J. D.; Basibuyuk, H. H.; Vincent, J. F. V. (Zool. J. Linn. Soc., 1998)

(untitled) - Schofield, R. M. S.; Nesson, M. H.; Richardson, K. A. (Naturwissenschaften, 2002)

(untitled) - Cribb, B. W.; Stewart, A.; Huang, H.; Truss, R.; Noller, B.; Rasch, R.; Zalucki, M. P. (Naturwissenschaften, 2008)

Modern Tribology Handbook, Vol. 2 - Bhushan, B. (CRC Press, 2000)

(untitled) - Weis-Fogh, T. (J. Mol. Biol., 1961)

(untitled) - Andersen, S. O.; Weis-Fogh, T. (Adv. Insect Physiol., 1964)

Cellular Solids: Structure and Properties - Gibson, L. J.; Ashby, M. F. (Pergamon Press, 1988)

(untitled) - Wang, R. Z.; Weiner, S. (J. Biomech., 1997)

(untitled) - Fowler, S. W.; Fisher, N. S. (Deep-Sea Res., Part A, 1983)

(untitled) - Dawkins, R.; Krebs, J. R. (Proc. R. Soc. London, Ser. B, 1979)

(untitled) - Smetacek, V. (Nature, 2001)

(untitled) - Turner, J. T. (Bull. Mar. Sci., 1978)

(untitled) - Friedrichs, L.; Hörnig, M.; Schulze, L.; Bertram, A.; Jansen, S.; Hamm, C. (Mar. Ecol. Prog. Ser., 2013)

(untitled) - Jansen, S. (Helgol. Mar. Res., 2008)

(untitled) - Kiørboe, T. (J. Plankton Res., 2011)